PENGARUH CONTENT MARKETING, ELECTRONIC WORD OF MOUTH DAN CITRA MEREK DI SOSIAL MEDIA TIKTOK TERHADAP MINAT BELI KONSUMEN (Studi Kasus Pada Konsumen Produk Wardah di Kota Semarang) - Muarrofah, Lailatul; Harminingtyas, Rudika (STIE PENA, 2025)
Abstract This research aims to analyze content marketing, electronic word of mouth, and brand image in relation to consumer purchase interest. The independent variables in this research are Content Marketing, Electronic Word of Mouth, and Brand Image. The dependent variable in this research is consumer purchase interest. The data sources in this research are primary and secondary data obtained by distributing questionnaires to respondents, namely Wardah product users aged 18-30 years in Semarang City. The sample used was 97 respondents. The sampling technique used was purposive sampling. The data analysis method uses the SPSS 25 program. The results show that Content Marketing has a positive and significant effect on Consumer Buying Interest with a significance level of 0.015 <0.05 and t count 2.469> t table 1.661, Electronic Word Of Mouth has a positive and significant effect on Consumer Buying Interest with a significance level of 0.002 <0.05 and t count 3.257 > t table 1.661 and Brand Image has a positive and significant effect on Consumer Purchase Interest with a significance level of 0.002 > 0.05 and t count 3.192 < t table 1.661 Results Content Marketing, Electronic Word Of Mouth and Brand Image simultaneously have a positive effect and significant for Consumer Purchase Interest as proven by F count 41.738 > F table 2.70 and significance level 0.000 < 0.05.Keywords: Content Marketing, Electronic Word Of Mouth, Brand Image, Consumer Purchase Interest.